Development of the applicative ones improves significantly the education - learning of the synthesis of proteins - Hidalgo-Hidalgo, Gilda E. (2019)
The present research work had as objective to evaluate the effects of the application development in the improvement of the levels of learning of the protein synthesis in the first year students of the Faculty of Obstetrics of the UNHEVAL - 2016. The type of investigation is Applied, whose level of research is experimental. The design is quasi experimental. The population for the development of the present research work consisted of the 86 students of the PAD of Obstetrics of the UNHEVAL enrolled in the first year 2016. To determine the sample of our investigation, we have used non-probabilistic sampling without norms or circumstantial, Because the researchers have chosen voluntarily 52 students of the Faculty of Obstetrics of the UNHEVAL de Huánuco. The results arrived at in the present study are: From the analysis it is inferred that the final average of the experimental group is 15, which shows that the achievement of the learning is satisfactory; And with respect to the control group the final average is 09, which shows marked difficulties for the development of the planned learning and needs more time of accompaniment and intervention of the teacher according to their rhythm and style of learning. The conclusions reached in the present study were: The development of an application demonstrates its effectiveness by significantly improving teaching-learning of protein synthesis in students of the Faculty of Obstetrics with respect to conceptual, procedural and attitudinal aspects.